Investigating the Use of Video Modeling to Teach the Expressive Use of Personal Pronouns to Children - Lichtblau, Katie (My University, 2013)
Many young children with autism engage in pronoun reversal and little research has been conducted to address this communication deficit. Video modeling has been used to teach a variety of communication and social skills to children with autism. The purpose of this study was to investigate the use of video modeling to teach expressive use of personal pronouns "my" and "your" to children with autism.
Color poster with text and graphs.
Keywords: Autistic children--Behavior modification; Video modeling; Personal pronouns--Teaching of; Posters